Speech results in post operative cases of cleft palate after speech therapy - Somusundaran N; Sharma RN (Journal of All India Institute of Speech and Hearing, 1970)
In this study, speech in cases of the cleft palate before and after speech therapy have been studied. A total of 22 cases were considered for inclusion in this study.  Those who had cleft involving the soft palate or soft palate and the hard palate with or without cleft of the lip and had undergone a surgical repair of the cleft palate in the Department of Plastic Surgery, K.G.'s Medical College, Lucknow, were selected. Only such patients whose surgical closure of the palate was complete and who had speech defects including articulation defects and/or excessive nasality, and who could attend a speech training programme for a period ranging from 3 weeks to 6 weeks, were considered